Dyskeratosis congenita with malignant transformation. (11th January 2011) - Ray, Jay Gopal; Swain, Niharika; Ghosh, Ranjan; Richa; Pattanayak (Mohanty), Sweta
Abstract : Dyskeratosis congenita (DC) is a rare genodermatosis characterised by a classic triad of dystrophic nails, reticular skin pigmentation and mucous membrane leukoplakic patches, which have a high rate of malignant transformation. The case report presented here deals with a sporadic case of DC without similar clinical presentation in the first-degree and second-degree relatives. Of note in this case, there was rapid malignant transformation in the non-homogeneous nodulo-speckled leukoplakic patch on the dorsum of the tongue.